Biochemical, immunological markers, histology and ultrastructural changes of open wound healing in rats treated with ethyl acetate extract of Zingiber zerumbet rhizomes - Asmah Hamid; Pek Lian Chong; Yun Ying Khor; Poh Ying Kong; Nur Rasyiqin Rasli; Nor Malia Abd Warif; Ahmad Rohi Ghazali; Nurul Farhana Jufri (Heliyon)
Research on plant-based wound healing agents has been one of the current developing areas in modern biomedical science. This study aimed to assess the effects of ethyl acetate extract of Zingiber zerumbet rhizome (ZZRE) on open wound healing activity in Wistar rats. Ninety male Wistar rats (220–320 g) were divided into three groups treated with phosphate buffered saline (PBS) (negative control), Solcoseryl gel (positive control), and 10 % ZZRE (treatment group), respectively. Six circular full-skin thickness wounds of 6.0 mm in diameter were induced bilaterally on the dorsal surface of each rat. Six rats were sacrificed on Day-1, Day-3, Day-6, Day-10 and Day-14 respectively from each group after wound induction. All data obtained are considered statistically significant at p < 0.05. Macroscopic observations showed that the 10 % ZZRE treated wounds healed faster compared to other groups. The wound closure percentage showed that the wound treated with 10 % ZZRE is significantly higher (p < 0.05) than the PBS group on Day-6, Day-10 and Day-14. Protein levels of the 10 % ZZRE group decreased significantly at Day-1 compared to the PBS group and significantly (p < 0.05) higher at Day-14 compared to both control groups. The hexosamine and uronic acid levels of the 10 % ZZRE group showed a significant (p < 0.05) decrease on Day-14. Conversely, hydroxyproline levels showed significant (p < 0.05) increase starting from Day-3 until Day-14. As for the immunological markers, the level of total TGF-β1 of the 10 % ZZRE group was significantly (p < 0.05) higher than the PBS group on Day-14, whereas the level of IL-10 on the wound tissue of the 10 % ZZRE group was significantly (p < 0.05) lower than the PBS group on Day-1 but significantly (p < 0.05) higher on Day-10 and Day-14 compared to both control groups. Histological observation showed that the wounds treated with 10 % ZZRE infiltrated with lesser inflammatory cells while collagen deposition was denser as compared to both control groups. Based on the result obtained, it is clearly proven that treatment of 10 % ZZRE on open wound healing in rats, showed that the extract was effective in healing the wound and accelerated the healing process. Therefore, the 10 % ZZRE tested has the potential to be developed as an alternative wound healing agent in the future.